PENGARUH POLA ASUH ORANG TUA DAN LINGKUNGAN SEKOLAH TERHADAP HASIL BELAJAR MATEMATIKA MELALUI MOTIVASI BELAJAR SISWA SMK NEGERI KECAMATAN SAMARINDA UTARA - Sainal Pakiding (PENDAS MAHAKAM: Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2016)
This study aims to determine (1) the influence of parents' parenting on learning outcomes of mathematics, (2) the influence of the school environment to the learning outcomes of mathematics, (3) influence student motivation for learning outcomes mathematics, (4) the effect of parenting parents against student motivation, (5) the impact of the school environment on student motivation, (6) the effect of parents' parenting on learning outcomes mathematics through motivation, (7) the impact of the school environment terhadapa result of learning mathematics through motivation, (8) the effect of parenting old, sekoah environment and motivation towards mathematics learning outcomes.This research is a quantitative research using cross sectional survey correlation. This study was conducted in March-May 2014. The study population was the students of class X SMK District of North Samarinda totaling 1,131 students with a sample size of 92 respondents and sampling using random sampling siple. The instrument used in this study was a questionnaire with data analysis techniques using path analysis (path analysis).The results of this study show that the first effect of parenting parents on learning outcomes of mathematics at 24.9%, the influence of the school environment on learning outcomes of the mathematics of 22.4%, a third influence students' motivation to learn math result by 21, 5%, the fourth influence parenting parents on the students motivation of 24.6%, the fifth school environment influence on the students motivation of 30.1%, the sixth parenting parents influence the learning outcomes of mathematics through the motivation of 53%, the seventh environmental influences schools the mathematics learning outcomes through motivation by 65% and eighth influence parenting parents, school environment and motivation to learn mathematics results by 48.3%.Keywords: Parenting Parents, School Environment, Learning Outcomes Mathematics, Motivation.